An efficient approach for solving the lot-sizing problem with time-varying storage capacities - Gutiérrez, J.; Sedeño-Noda, A.; Colebrook, M.; Sicilia, J. (European journal of operational research, 2008)
We address the dynamic lot size problem assuming time-varying storage capacities. The planning horizon is divided into T periods and stockouts are not allowed. Moreover, for each period, we consider a setup cost, a holding unit cost and a production/ordering unit cost, which can vary through the planning horizon. Although this model can be solved using O( T 3) algorithms already introduced in the specialized literature, we show that under this cost structure an optimal solution can be obtained in O( T log T) time. In addition, we show that when production/ordering unit costs are assumed to be constant (i.e., the Wagner–Whitin case), there exists an optimal plan satisfying the Zero Inventory Ordering (ZIO) property.